2011
DOI: 10.1080/0952813x.2010.506300
|View full text |Cite
|
Sign up to set email alerts
|

Research on the evolutionary game of environmental pollution in system dynamics model

Abstract: Environmental pollution abatement is a complex project. A system dynamics (SD) model is built for studying a mixed-strategy evolutionary game between the government that manages environmental pollution and the firm that generates contamination during their production processes. The stability analysis and SD simulation results show that evolutionary equilibrium (EE) does not exist with a static penalty. Therefore, a dynamic penalty is suggested in the SD model for equilibrium stabilisation and improvement in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 16 publications
(18 reference statements)
1
30
0
Order By: Relevance
“…Many research trials have proved that correlating penalties with their unlawful behavior ratio can effectively restrain the fluctuations (Wang et al, 2011;Cai, 2010Cai, , 2011. Therefore, the dynamic penalty control scenario was proposed to restrain the fluctuations, namely, the SACMS make penalties dynamically according to coal enterprises' unlawful production ratio and LRDCMS' dereliction ratio, which were shown in the following formula.…”
Section: Stability Analysis and Check Under The Dynamic Penalty Contrmentioning
confidence: 99%
“…Many research trials have proved that correlating penalties with their unlawful behavior ratio can effectively restrain the fluctuations (Wang et al, 2011;Cai, 2010Cai, , 2011. Therefore, the dynamic penalty control scenario was proposed to restrain the fluctuations, namely, the SACMS make penalties dynamically according to coal enterprises' unlawful production ratio and LRDCMS' dereliction ratio, which were shown in the following formula.…”
Section: Stability Analysis and Check Under The Dynamic Penalty Contrmentioning
confidence: 99%
“…For instance, Wang et al (2011) used SD to simulate an evolutionary game between the government and enterprises regarding the management of environmental pollution. A dynamic penalty was suggested as an efficient surveillance measure to reduce environmental contamination by enterprises.…”
Section: Application Of Game Theory To Green Consumptionmentioning
confidence: 99%
“…Enterprises are also significant stakeholders in reducing carbon emissions (Wang et al, 2011;Tian et al, 2014). Investigations of the sales of carbon-labeled products have indicated that consumers would like to pay more for green products .…”
Section: Introductionmentioning
confidence: 99%
“…The findings have proved the dilemmas in terms of carbon emissions. Some other relevant studies in terms of environmental issues and the revolutionary game theory include Wang et al [9], Barari et al [10], Dai et al [11], Zhu et al [12], Wang et al [13]. Even in other empirical studies with different methods such as Bao et al [14], Guo and Wang [15], Chen [16], Cao [17].…”
Section: Introductionmentioning
confidence: 98%